STRATEGI MITRA BENTALA DALAM MENUMBUHKAN KESADARAN DAN KESIAPSIAGAAN MITIGASI BENCANA MASYARAKAT DESA MAJA KABUPATEN LAMPUNG SELATAN - Salwa Fitria widianti; Siti Badi’ah; Luthfi Salim (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study aims to analyze the forms of disaster mitigation strategies implemented by Mitra Bentala in Maja Village, South Lampung Regency, and to examine the social transformation that occurred in the community following the intervention. The strategies included disaster education, evacuation simulations, the formation of Disaster Resilient Villages (Destana), the construction of evacuation routes, and environmental empowerment programs such as waste banks and seed nurseries. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted inductively using Pierre Bourdieu's theory of social practice, incorporating the concepts of habitus, capital, and field. The findings indicate that the strategies fostered the emergence of a new habitus within the community a collective disposition toward risk awareness and preparedness. The interaction between the community's habitus, various forms of capital (social, symbolic, economic), and the village as a field of practice produced a social transformation reflected in increased disaster readiness, collective awareness, and strengthened community structures. These results demonstrate that community-based mitigation strategies can effectively generate adaptive and sustainable social change within disaster-prone rural contexts.